Patients’ Profile Regarding Physiatric Management of Facial Palsy in a Tertiary Care Hospital (Journal of Bangladesh College of Physicians and Surgeons, 2018)
Introduction: Facial palsy is commonly treated by various physical therapy strategies and devices, but there are many questions about the profile of patients with facial nerve palsy. The aim of the study was to outline profile of patients with facial palsy receiving Physiatric management.Materials and Methods: A retrospective hospital recordsbased study was carried out at the department of Physical Medicine and Rehabilitation (PMR) in National Institute of Neurosciences and Hospital (NINS&H), Dhaka for the period of two year from 1st July 2013 to 30th June 2015.Results: Total 5240 patients were studied, of which 58.87% were male and 41.13% were female. Maximum patients Journal of Bangladesh College of Physicians and Surgeons Vol. 36, No. 1, January 2018 (26.58%) belong to 31-40 years of age. Maximum patients (72.36%) came from Dhaka city and most of the studied patients were housewife (31.68%). Largest disease group was Bell’s palsy (56.2%). Regarding disease pattern, 61.18% of patients peripheral nervous system (PNS) and 38.82% central nervous system (CNS) condition. Among etiologies of Facial palsy, 56.2% Bell’s palsy, 36.95% stroke, 3.40% Guillain-Barre’ syndrome, 2% traumatic, 0.52% were Ramsay-Hunt syndrome.Conclusion: Profile of patients should be considered for Physiatric management of Facial nerve palsy.J Bangladesh Coll Phys Surg 2018; 36(1): 16-19